Effects of Neonicotinoid Pesticide Exposure on Human Health: A Systematic Review - Cimino, Andria M. (Environ Health Perspect, 2016)
BACKGROUND: Numerous studies have identified detectable levels of neonicotinoids (neonics) in the environment, adverse effects of neonics in many species, including mammals, and pathways through which human exposure to neonics could occur, yet little is known about the human health effects of neonic exposure. OBJECTIVE: In this systematic review, we sought to identify human population studies on the health effects of neonics. METHODS: Studies published in English between 2005 and 2015 were searched using PubMed, Scopus, and Web of Science databases. No restrictions were placed on the type of health outcome assessed. Risk of bias was assessed using guidance developed by the National Toxicology Program’s Office of Health Assessment and Translation. RESULTS: Eight studies investigating the human health effects of exposure to neonics were identified. Four examined acute exposure: Three neonic poisoning studies reported two fatalities (n = 1,280 cases) and an occupational exposure study of 19 forestry workers reported no adverse effects. Four general population studies reported associations between chronic neonic exposure and adverse developmental or neurological outcomes, including tetralogy of Fallot (AOR 2.4, 95% CI: 1.1, 5.4), anencephaly (AOR 2.9, 95% CI: 1.0, 8.2), autism spectrum disorder [AOR 1.3, 95% credible interval (CrI): 0.78, 2.2], and a symptom cluster including memory loss and finger tremor (OR 14, 95% CI: 3.5, 57). Reported odds ratios were based on exposed compared to unexposed groups. CONCLUSIONS: The studies conducted to date were limited in number with suggestive but methodologically weak findings related to chronic exposure. Given the wide-scale use of neonics, more studies are needed to fully understand their effects on human health. CITATION: Cimino AM, Boyles AL, Thayer KA, Perry MJ. 2017. Effects of neonicotinoid pesticide exposure on human health: a systematic review. Environ Health Perspect 125:155–162; http://dx.doi.org/10.1289/EHP515